2017
DOI: 10.1016/j.cedpsych.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

From externalizing student behavior to student-specific teacher self-efficacy: The role of teacher-perceived conflict and closeness in the student–teacher relationship

Abstract: Data gathered from a longitudinal study within regular upper elementary schools were used to evaluate a theoretical model within which teachers' perceptions of conflict and closeness in the student-teacher relationship were considered as the intermediary mechanisms by which individual students' externalizing behavior generates changes in teachers' student-specific self-efficacy beliefs (TSE) across teaching domains. Surveys were administered among a Dutch sample of 524 third-to-sixth graders and their 69 teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 64 publications
(135 reference statements)
0
50
0
2
Order By: Relevance
“…Specifically, studies of teachers’ contributions to positive teacher–child relationships have shown that when teachers interact with students in ways that demonstrate interest in students’ emotions and activities, there is more closeness in the relationship [ 51 , 52 ]. Additionally, when teachers have more self-efficacy, especially for working with individual students, they are likely to feel more positively toward students and report more teacher–child closeness [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies of teachers’ contributions to positive teacher–child relationships have shown that when teachers interact with students in ways that demonstrate interest in students’ emotions and activities, there is more closeness in the relationship [ 51 , 52 ]. Additionally, when teachers have more self-efficacy, especially for working with individual students, they are likely to feel more positively toward students and report more teacher–child closeness [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the image typically held by general education primary teachers that students with SEBD are difficult to handle, based on the students' disruptive behaviour (Goei and Kleijnen 2009). This in turn often results in a vicious circle and a poor teacher-student relationship (Zee, de Jong, and Koomen 2017). Another possibility regarding teacher-student trust issues could be that the teacher does not see the student as a victim but rather as a bully (Novick and Isaacs 2010;Oldenburg, Bosman, and Veenstra 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Students felt ashamed or feared that the teacher would dismiss their story as not credible in those studies. A study by Zee, de Jong, and Koomen (2017) found that the perception of the teacher-student relationship, especially with regard to conflicts, is most likely the result of their own behaviour and characteristics rather than the attitude of the teachers. Zee et al (ibid) also found that the teachers' perceptions are formed from teacher and student characteristics, especially for boys and students showing externalising behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we focused on classroom management self‐efficacy , which is the teacher's belief in their ability to manage child behavior and disruptions in the classroom, including having children follow classroom expectations (Tschannen‐Moran & Hoy, 2001), given that it is most relevant to managing children's behavior. Zee, de Jong, and Koomen (2017) found that challenging child behavior impacted child‐specific teacher self‐efficacy for classroom management, which led to higher rates of conflict in teacher–child relationships. Theoretical notions and prior research provide support for the mediating role of self‐efficacy in the relationship between racial mismatch and teachers' perceived conflict with children.…”
Section: Self‐efficacy As a Mediatormentioning
confidence: 99%